Gay as classroom practice: A study on sexuality in a secondary language classroom - Angelica Simonsson; Petra Angervall (Linköping University Electronic Press, 2016)
In this study conceptions of sexuality in classroom praxis are investigated. Sexuality and education is a growing field of research, in Sweden as well as internationally, something which has been recently represented also in Confero, not least in the contributions in the special issue "Queering School, Queers in School". In the introduction to an anthology on gender, sexuality and education, Carlson and Meyer point out that school, as an institution, plays an important role in society when it comes to regulating gender and sexuality since school is a producer of differences in terms of "separable binary oppositions" such as man-woman and straight-gay, that are easily understood within the dominating culture and where one in each couple is usually more highly valued than the other. Carlson and Meyer further assert that school as an institution, in this way, produces gender and sexuality. One example of this is presented by Dalley and Campbell, who in their study of pupil interaction in high school conclude that the male pupils produce heterosexuality, whether actual or pretended, as normal by referencing homosexuality as abnormal. Our reading of these studies indicates that within both formal and informal schooling, meaning and knowledge is produced through everyday practices in which conceptions of gender and sexuality are crucial. In these practices, heterosexuality holds a position as taken-for-granted and normative.